2020
DOI: 10.1177/0300060520927874
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of low-dose scan parameters in dual-energy computed tomography for displaying the anterior cruciate ligament

Abstract: Objective This study was performed to assess low-dose scan parameters in dual-energy computed tomography (CT) for displaying the anterior cruciate ligament. Methods Dual-energy CT scans with low and standard dose parameters, respectively, were performed in nine human knee joint specimens. Eighteen imaging data sets for cruciate ligament specimens were obtained and processed. Statistical analysis was performed for signal-to-noise ratios of the CT images and subjective scores. Results Comparable signal-to-noise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Fickert (10) and Peltola et al (11) also successively reported the diagnosis of a cruciate ligament injury on piglet animal models and for patients using DECT. Our previous study (12) found a new potential sign of DECT in diagnosing ACL injury, i.e. diminution sign-on dual-energy color mapping, which preliminarily proved the feasibility of this method.…”
Section: Introductionmentioning
confidence: 70%
“…Fickert (10) and Peltola et al (11) also successively reported the diagnosis of a cruciate ligament injury on piglet animal models and for patients using DECT. Our previous study (12) found a new potential sign of DECT in diagnosing ACL injury, i.e. diminution sign-on dual-energy color mapping, which preliminarily proved the feasibility of this method.…”
Section: Introductionmentioning
confidence: 70%
“… 26 Dual‐energy CT has a growing role in diagnosing gout and bone marrow edema. Also, Bai et al 27 displayed the anterior cruciate ligament using dual‐energy CT. In the present study, two components of CC ligament could be distinctly seen on the color‐coding dual‐energy CT images, and we proved in another study that CC ligament was best shown at 40 keV.…”
Section: Discussionmentioning
confidence: 99%